A spatial Diff-in-Diff analysis of the impact of sugarcane producion on respiratory diseases - Andre Chagas; Carlos Azzoni; Alexandre Almeida (European Regional Science Association (ERSA), 2015)
The production of ethanol and sugar from sugarcane has sharply increased in Brazil in the last 20 years, in a process of substitution of biofuel for fossil fuels. The increase in the production and the expansion of the cultivated area might have impacts on human health and employment, especially at the regional level. So far, the harvest is basically manual, involving low-skill workers. The burning of the cane is meant to increase labor productivity and has been traditionally executed. However, the burning generates a massive quantity of smoke that spread in the region, reaching neighboring cities, thus becoming a potential threat to the human health. The objective of this paper is to measure the impact of sugarcane producing, and indirectly, the burning associated to this production, on respiratory problems. We work with a balanced panel of 644 municipalities, from 2002 to 2013. We propose to use a spatial difference-in-difference method, to control for the effect of sugarcane burning on non-producing regions in the vicinity of producing regions. We conclude that sugar cane burning significantly increases the incidence of respiratory problems in producing regions. The use of a spatial diff-in-diff model allowed us to find out that the effect on non-producing nearby regions is also significant and quantitatively relevant. We make a Monte Carlo simulation and conclude that our method is able to identify effects over non treated higher than 50%.Our empirical results suggest that the effect over non-treated region is about 3/4 of the effect on producing aereas.
Keywords: C14; C21; Q18; 330; Sugarcane Producing; Health Condition; Spatial Econometrics; Spatial Diff-in-Dif